The reason of degradation in electrical properties of ZnO:Al thin films annealed with various post-annealing temperature - Kim, Deok-Kyu; Kim, Hong Bae (Current applied physics, 2013)
ZnO:Al (AZO) thin films were deposited on glass substrates by RF magnetron sputtering at room temperature and post-annealed in rapid thermal annealing (RTA) system. The effect of post-annealing temperature on the structural, optical, and electrical properties was investigated. As the post-annealing temperature increased, electrical conductivity is deteriorated due to a decrease in the mobility or carrier concentration, gradually. According to X-ray photoelectron spectroscopy (XPS) analysis, the behavior of mobility and carrier concentration is attributed to increase the O2 absorption on film surface, which act as rising the barrier potential at the low post-annealing temperature (200 °C) and reducing the density of donor-like defects at the high post-annealing temperature (400 °C). In case of post-annealing, the minimization of O2 absorption is a very important factor to obtain better electrical properties. •The O2 absorption played a barrier potential at low post-annealing temperature.•The O2 absorption reduced the density of donor-like defects at high post-annealing temperature.•The minimization of O2 absorption is a very important factor to obtain better electrical properties.